A first course in applied mathematics - Rebaza, Jorge (Hoboken : John Wiley & Sons, 2012)
Explore real-world applications of selected mathematical theory, concepts, and methods Exploring related methods that can be utilized in various fields of practice from science and engineering to business, A First Course in Applied Mathematics details how applied mathematics involves predictions, interpretations, analysis, and mathematical modeling to solve real-world problems. Written at a level that is accessible to readers from a wide range of scientific and engineering fields, the book masterfully blends standard topics with modern areas of application and provides the needed foundation.
A First Course in Applied Mathematics; CONTENTS; Preface; 1 Basics of Linear Algebra; 1.1 Notation and Terminology; 1.2 Vector and Matrix Norms; 1.3 Dot Product and Orthogonality; 1.4 Special Matrices; 1.4.1 Diagonal and triangular matrices; 1.4.2 Hessenberg matrices; 1.4.3 Nonsingular and inverse matrices; 1.4.4 Symmetric and positive definite matrices; 1.4.5 Matrix exponential; 1.4.6 Permutation matrices; 1.4.7 Orthogonal matrices; 1.5 Vector Spaces; 1.6 Linear Independence and Basis; 1.7 Orthogonalization and Direct Sums; 1.8 Column Space, Row Space, and Null Space.
Includes bibliographical references and index.
Print version record.
Keywords: Computer simulation; Mathematical models; MATHEMATICS -- Applied; Mathematical models; Computer simulation; MATHEMATICS -- Essays; MATHEMATICS -- Pre-Calculus.; MATHEMATICS -- Reference; Computer simulation; Mathematical models; Mathematisches Modell; Computersimulation; Electronic books